ANALISIS IMPLEMENTASI MODEL BLENDED LEARNING DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Sopyan Hendrayana; Tati Heriati; Desviana Prakawati; Anisa Istiqomah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
ABSTRACT The problem that often arises in the field of education during this pandemic is the learning process carried out in the "new normal" era, namely the learning model used by teachers in delivering learning materials that are expected to increase motivation and learning outcomes of elementary school students. Then the problem of technology-based tools as a support for distance learning that not all students have, for example, gadgets as a communication tool between teachers and students because usually in villages the use of communication tools is inadequate and there are many obstacles, one of which is a signal, then for problems Another is when face-to-face learning is required to carry out health protocols, while the number of students is relatively large which can cause a crowd, especially when there are students who are confirmed positive for Covid 19. So we need a learning model that can accommodate services. Optimal learning. This research was conducted using a qualitative research method, a type of literature study. The blended learning model is a model that uses the integration of face-to-face learning with online-based learning (in a network). The teacher has a role as a facilitator and parents as a supporter of children's learning activities. The implementation of this blended learning model has steps and syntax including; 1) seeking of information, 2) acquisition of information, 3) synthesizing of knowledge. Learning using the blended learning model is carried out in a varied and innovative manner, it can motivate students to take part in learning well and as evidenced by the results of the study, there is an increase in the learning outcomes of elementary school students. Keywords: Blended Learning, Motivation, Learning Outcomes ABSTRAK Permasalahan yang sering muncul dalam bidang pendidikan di masa pademi ini adalah proses pembelajaran yang dilakukan pada era ”new normal” yaitu mengenai model pembelajaran yang dipakai guru dalam menyampaikan materi pembelajaran yang diharapkan dapat meningkatkan motivasi dan hasil belajar siswa SD. Kemudian masalah mengenai alat berbasis teknologi sebagai pendukung untuk melakukan pembelajaran jarak jauh yang tidak semua siswa memilikinya, misal gedget sebagai alat komunikasi antara guru dan siswa karena biasanya di desa untuk penggunaan alat komunikasi kurang memadai dan banyak sekali kendala salah satunya adalah sinyal, kemudian untuk masalah lainnya yaitu saat pembelajaran tatap muka langsung maka wajib menjalankan protokol kesehatan, sedangkan jumlah siswa relatif banyak yang dapat menimbulkan kerumunan, terlebih ketika terdapat siswa yang terkonfirmasi positif covid 19. Maka membutuhkan model pembelajaran yang dapat mengakomodasi layanan pembelajaran secara optimal. Adapun penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif jenis studi literatur. Model blended learning merupakan model yang menggunakan keterpaduan dari pembelajaran tatap muka dengan pembelajaran berbasis online (dalam jaringan). Guru memiliki peranan sebagai fasilitator dan orang tua sebagai penyokong kegiatan belajar anak. Pelaksanaan model blended learning ini terdapat langkah serta sintak diantaranya; 1) seeking of information, 2) acquisition of information, 3) synthesizing of knowledge. Pembelajaran dengan menggunakan model blended learning dilakukan dengan variatif dan inovatif dapat membuat siswa termotivasi untuk mengikuti pembelajaran dengan baik dan terbukti dari hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa SD. Kata kunci: Blended Learning, Motivasi, Hasil Belajar